2022
DOI: 10.5336/dentalsci.2021-87792
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Gagging in Children and the Association Between Gagging and Dental Fear: A Cross-Sectional Study

Abstract: Gag reflex is a natural defense mechanism that prevents the passage of unwanted objects to the aspiratory system (trachea, larynx, and oropharyngeal airway). 1 Intraoral areas, posterior pharyngeal wall, palatoglossal and palatopharyngeal folds, palate, uvula and root of tongue known as "trigger zones" in the formation of the reflex. 2 With the stimulation of these points, the transmission of the cranial nerves (notably, the pharyngeal nerve) to the medulla oblongata with sensory neurons causes irregular and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(10 citation statements)
references
References 21 publications
3
7
0
Order By: Relevance
“…7 The prevalence of gag reflex among Turkish children was examined in one study, and the prevalence was reported as 29.5% varying in severity from 1 to 3 in children aged between 6 and 14 years. 16 In this present study, the prevalence of gag reflex among 7-14 years old Turkish children was found as 34.1%. The higher prevalence of this study is most likely because of differences between measurements of gagging.…”
Section: Discussionsupporting
confidence: 48%
See 4 more Smart Citations
“…7 The prevalence of gag reflex among Turkish children was examined in one study, and the prevalence was reported as 29.5% varying in severity from 1 to 3 in children aged between 6 and 14 years. 16 In this present study, the prevalence of gag reflex among 7-14 years old Turkish children was found as 34.1%. The higher prevalence of this study is most likely because of differences between measurements of gagging.…”
Section: Discussionsupporting
confidence: 48%
“…17 In another studies, younger children have a greater tendency to gag. 7,16 Besides that, Katsouda et al(2017) did not find any significant difference in children aged between 8 and 14 years. 8 To give accurate answers to the questions asked in the current study, children between the ages of 7-14 were selected, and the difference between children who gagged or did not gag was not found statistically significant.…”
Section: Discussionmentioning
confidence: 74%
See 3 more Smart Citations